Addressing food insecurity and climate change in Malaysia: Current Evidence and Way Forward - Jemilah, Mahmood *; Rajaram, Nadia N *; Guinto, Renzo R * (Penerbit Universiti Sains Malaysia, 2022)
Access to sufficient, nutritious food is an urgent, mounting global problem that has been exacerbated by the COVID-19 pandemic. In 2020, up to 30% of the global population faced food insecurity, a 4% increase from the preceding year, with great variation across regions (1). The highest levels of food insecurity were reported in the African continent, where more than half the population (59%) reported poor access to food (1). The largest impact of the pandemic, however, was observed in Latin America and the Caribbean, where the pandemic led to an almost 10% increase in food insecurity in just over a year, resulting in 41% of the population living with food insecurity (1). In Asia, the prevalence of food insecurity increased by 3% to 26% in 2020 (1). The pandemic highlighted how vulnerable current food systems are, especially in emerging economies that rely on large-scale agriculture and international food trade. Without intervention, the global food-insecure population is expected to rise by another 10% by 2050 (2), or more if another global catastrophe strikes.